A case using patterns to identify bussiness processes in a company - Rekuć, Witold; Szczurowski, Leopold (Przypadek zastosowania wzorców do identyfikacji procesów biznesowych w przedsiębiorstwie, 2011)
The application of patterns in the initial analysis of the business processes has been discussed. It was carried out in relation to the information technology application and infrastructure development in a company. A specific case of such a research, performed fora transport company, has been described. The transport company sells fuel in a holding. The composition (structure) of the used pattern has been provided and the results received in this specific case have been generalized
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2011, Nr 206, s. 164-172
Keywords: bussiness process; process pattern; bussiness analysis; proces biznesowy; wzorzec procesu; analiza procesów biznesowych